Meneladani Gaya Kepemimpinan Nabi Muhammad SAW dalam Pendidikan Islam - Mujahid, Kasori; Azis, Muhamad Abdul; Chabib, Mudzakir (Lembaga Yasin AlSys, 2025)
Prophet Muhammad SAW serves as a role model for all humanity, particularly in the area of leadership. His leadership style is a prime example of an effective leadership system, which successfully brought about significant transformation in the Arab community, who were living in ignorance and darkness at that time. The principles of his leadership, including siddiq (honesty), amanah (trustworthiness), tabligh (communication), and fathanah (wisdom), are applicable across various situations and contexts. Islamic education today faces significant challenges, one of which is the crisis of leadership. This study aims to explore the application of the Prophet's leadership model within the context of contemporary Islamic education. The objective of this journal is to describe the leadership style of Prophet Muhammad SAW and its relevance to modern times. The research employs a qualitative method with a descriptive and analytical approach, drawing data from diverse sources such as the Qur'an, Hadith, and Islamic historical texts. The leadership style of Prophet Muhammad SAW has proven to be effective in creating positive change within society, making it an exemplary model for current leaders in fulfilling their roles and responsibilities.